Sistema de información web sobre las características socioeconómicas del alumnado de la ESPAM MFL como apoyo a la toma de decisiones - Mendoza Mendieta, María Paola (2017)
The development of this thesis was aimed at creating a web system that manages the socioeconomic characteristics of the students of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López to contribute to the institution's authorities with organized, structured and accessible information to make a decision. Quantitative and qualitative methods were used in the analysis of the socioeconomic variables of the same ones, they allowed to classify the obtained information, to generate reports and the bibliographic method for the theoretical sustenance of the researchers and the readers. The system "Management of Surveys" is developed through the agile SCRUM methodology, made up of three phases; In the planning phase, the actors, functional and non-functional requirements were defined as well as establishing the team's roles. In the execution phase, sprints were elaborated and the development of the technological tools implementation system such as Visual Studio 2015 with the ASP.NET Development Framework and the SQL Server 2012 database manager; And in the last phase inspection and adaptation were performed tests of functionality and implementation of the software. The result obtained is a computer system that organizes and gives access to socioeconomic information of the student based on the indicators in the chart; Information that guides the comprehensive policy of student welfare, services for baseline surveys in research programs, or linking; In addition, it will improve institutional evaluation indicators.